(untitled) (Homoeopathy for All, 2026)
Allergic rhinitis is a common disorder that is usually a long standing condition that often goes undetected in the primary-care setting. The classical manifestation of the disorder are nasal congestion, nasal itch, rhinorrhea and sneezing. A thorough history, physical examination and allergen skin testing are important for establishing the diagnosis of allergic rhinitis. Rhinitis is classified into one of the following categories according to etiology: IgE-mediated (allergic), autonomic, infectious and idiopathic (unknown). This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of allergic rhinitis.